Evaluation of Public Street Lighting In Bengkayang Regency - Yusuf, Muhammad; Arsyad, Muhammad Iqbal; Danial, Danial (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Public street lighting (PJU) is a public lighting installation and is usually installed on roads, bridges and certain places, such as parks and other public places. Public Street Lighting Lamps (LPJU) are lamps used to illuminate roads at night to make it easier for pedestrians, cyclists and vehicle drivers to see more clearly the road/terrain that will be traversed at night, thereby increasing traffic safety and user comfort. roads and provide security from criminal activities. On the highways in Sungai Betung, Bengkayang and Ledo sub-districts in Bengkayang Regency, in the existing condition, 84 PJUs are installed with single ornament light points, the lights used are 150 watt SON-T with an illumination of 15.67 lux, and 60 watt LEDs with an illumination of 7 .69 lux, with a road width of 4-5 and a distance between poles of 45-50 meters requires energy of 109.08 kWh/day. In the existing condition there are 24 light points that do not turn on. After the arrangement was carried out, the results were 50 watt and 60 watt LED lights with a pole height of 7 meters, the angle of the ornamental handlebar was 16,260 which produced illumination of 5.7 lux to 6.85, the number of light points was 108 points, the power The required energy consumption is 6.07 kWh and the required energy consumption is 72.85 kWh/day. Based on the results of the evaluation, the overall energy savings were 36.23 kWh/day. The results of this research indicate that the arrangement by replacing LED lights is feasible according to BSN SNI 7391:2008